Legends of the mahasiddhas: lives of the Tantric masters - Beer, Robert; Abhayadatta ca. 11./12. Jh.; Dowman, Keith (Inner Traditions, 2014)
"A richly illustrated collection of stories about the mahasiddhas, spiritual adventurers who attained enlightenment and magical powers by disregarding convention. A modern translation of ancient legends that reveals the human qualities of the rebellious saints known as siddhas and the vital elements of their philosophy. Recounts stories of enlightened masters from all walks of life, including a washerman, a thief, a conman, a gambler, and a whore, and the magical and "crazy" deeds of each, such as walking through walls, flying, talking with birds, and turning people to stone. Richly illustrated with paintings of the tantric saints by artist Robert Beer. Offering a modern translation of "The Legends of the Eighty-four Mahasiddhas," a 12th-century Tibetan text, translator Keith Dowman shares stories of the spiritual adventurers, rebellious saints, and enlightened tantric masters of ancient India known as "siddhas." He shows how the mahasiddhas arose from the grassroots of society and represented an entire spectrum of human experience. Counted among the greatest of the siddhas are a washerman, a cowboy, a thief, a conman, a gambler, and a whore, all extraordinary men and women who attained the goal of their meditations, as well as enlightenment and magical powers, by disregarding convention and penetrating to the core of life. Recounting the magical and "crazy" deeds of the mahasiddhas, such as walking through walls, flying, talking with birds, and turning people to stone, Dowman reveals the human qualities of the tantric masters and the vital elements of the siddhas' philosophy of nonduality and emptiness. Richly illustrated with paintings of the tantric saints by artist Robert Beer, these stories of the mahasiddhas show us a way through human suffering into a spontaneous and free state of oneness with the divine"--